Animal-Human Relationships in Medieval Iceland : From Farm-Settlement to Sagas - Evans Tang, Harriet J. (Woodbridge, Suffolk ; Rochester, NY : D.S. Brewer, 2022)
A multi-disciplinary investigation of the links between people and animals, in reality and representation.
Print version record.
Online resource; title from digital title page (viewed on September 15, 2022).
Includes bibliographical references (pages [215]-238) and index.
JSTOR
Keywords: Icelandic literature -- History and criticism; Human-animal relationships in literature; Human-animal relationships -- Iceland -- History -- To 1500.; Agriculture -- Iceland -- History -- To 1500.; Littérature islandaise -- Histoire et critique; Relations humain-animal dans la littérature.; Agriculture -- Islande -- Histoire -- Jusqu'à 1500.; Icelandic literature; Human-animal relationships in literature; Agriculture; Human-animal relationships; Iceland; To 1500; Criticism, interpretation, etc; History